An analysis of nursing students’ ethical conflicts in a hospital - Eckardt, Margit (Nursing ethics, 2019)
Background:Education can be taken as a key factor in transmission of a value tradition in healthcare. In professional and educational contexts, transmission of values appears to be a kind of guarantee for an occupational group’s professional identity, awareness and ethical integrity. Given the positives of such transmission of value traditions, one can also pay attention to conflicts between the professional tradition and individuals who are brought into that tradition.Objectives:How does mediation of value tradition in healthcare education appear out of the students’ perspective based on their own narratives?Research design and participants:Students’ texts were analysed through a combination of contrastive discourse analysis and sociohistorical description and then evaluated from an ethical perspective. Data were collected from the annual electronic feedback given by students after their clinical practice at a University Hospital.Ethical considerations:Organizational approval was received. Information about the voluntary nature of participation was a part of the feedback tool.Findings:The analysis points to the fact that there is a definite theme in the students’ experiences that both the previous research has neglected and that stands in conflict with the current tradition of healthcare education in Finland. That theme can be summarized in the experience of ‘losing one’s identity’, and it is expressed in a request to experience of ‘losing one’s identity’ and it is expressed in a request to have a right to ‘use one’s own name’ also as a healthcare professional.Discussion and conclusion:Being addressed by one’s name is to make the person directly involved and responsible, realizing that that person’s perspective is of importance to the way the world is. We argue that this theme (my name) is of ethical importance and could have empowering potentiality when used in an ethically sound way.